1999
DOI: 10.1109/10.748987
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve electrode positioning and safety in cochlear implants

Abstract: An injection-molded internal supporting rib has been produced to control the flexibility of silicone rubber encapsulated electrodes designed to electrically stimulate the auditory nerve in human subjects with severe to profound hearing loss. The rib molding dies, and molds for silicone rubber encapsulation of the electrode, were designed and machined using AutoCad and MasterCam software packages in a PC environment. After molding, the prototype plastic ribs were iteratively modified based on observations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 32 publications
1
36
1
1
Order By: Relevance
“…The data was used by Cochlear™ to form the cavity of the ST model, which is approximately 9 mm (from cochleostomy to Basal turn area) by 6 mm (diameter about modiolus), with a depth of 1.5 mm. In previous insertion studies, synthetic replicas have been created from human cadavers [4], [5], [7]. In this paper, the model used was machined from Polytetrafluoroethylene (Teflon).…”
Section: ) Model Of the Human Scala Tympani (St)mentioning
confidence: 99%
See 4 more Smart Citations
“…The data was used by Cochlear™ to form the cavity of the ST model, which is approximately 9 mm (from cochleostomy to Basal turn area) by 6 mm (diameter about modiolus), with a depth of 1.5 mm. In previous insertion studies, synthetic replicas have been created from human cadavers [4], [5], [7]. In this paper, the model used was machined from Polytetrafluoroethylene (Teflon).…”
Section: ) Model Of the Human Scala Tympani (St)mentioning
confidence: 99%
“…Researchers have identified key elements that affected force output during electrode insertion, including implant design and insertion behavior [4], [5], restoration forces [4], carrier stiffness [4], [6], [8], contact pressure at the tip [6], as well as coefficient of friction between a lubricated model and silicone tip [5]. Synthetic models of the ST have been used for the purpose of insertion force measurement during cochlear implantation [4], [5], [7]. Existing studies have shown the importance of quantifying force components and the assessment of electrode trajectories for specific electrode designs, for the minimization of trauma [4], [5], [8]- [17], optimal electrode placement [1], [4], [9], [13], [14], [18]- [21], and to avoid damage to the electrode [8], [11], [12].…”
Section: A Measurement Of Insertion Forcesmentioning
confidence: 99%
See 3 more Smart Citations